Simulation study on bandwidth utilization of diffserv traffic using ns-2 - Din N.M.; Hakimie H.; Balasubramaniam N.; Ishak Z. (2023)
This paper describes simulation study of bandwidth utilization of DiffServ Traffic in the Internet using ns-2. The study investigates the behavior of traffic based on Diffserv traffic class types, i.e. Expedited Forwarding (EF), Assured Forwarding (AF) and Best Effort (BE) traffic. The EF traffic is represented by real time constant bit rate premium traffic, AF by the real time variable bit rate assured and BE non-real time best effort traffic. Single flow and aggregate flows were compared in the study. The bandwidth wastage is most evident in the AF real time variable bit rate aggregate traffic. 2008 IEEE.